Asesmen Diagnostik Non-Kognitif Gaya Belajar Siswa SMP Kelas 7 di Lembang, Indonesia: Non-Cognitive Diagnostic Assessment of Learning Styles for 7th Grade Junior High School Students in Lembang, Indonesia - Huda, Ali Anhar Syi’bul; Nurhuda, Abid (Nusantara Journal of Behavioral and Social Science, 2023)
Learning style is a way of receiving, understanding, and processing information from each student in the learning process. In its development, learning styles are broadly (generally) divided into visual, auditory, and kinesthetic learning styles. One of the efforts that can be made to find out the learning style of each student is by non-cognitive diagnostic assessment, especially in the framework of the independent curriculum learning becomes one of the main and most important things. Non-cognitive diagnostic assessment is very helpful for educators in mapping learning needs and goals according to the learning styles of their students. SMPN 3 Lembang did the same thing by conducting non-cognitive diagnostic tests on 318 students as samples in the study. This research uses a qualitative approach with descriptive methods, while the data collection tools are taken from the results of the non-cognitive diagnostic test of learning styles of students in grades 7D-7K at SMPN 3 Lembang in the 2023/2024 academic year. The results of the study concluded that the learning style of students in grades 7D-7K at SMPN 3 Lembang was most dominant in the visual learning style with a percentage of 46% (148 students), in second place was the kinesthetic learning style of 40% (126 students), and the auditory learning style was 14% (44 students). It is expected that educators can use learning styles that can stimulate students' visual learning styles such as the use of demonstration teaching methods, practicum, observation of the surrounding environment, and others. Abstrak: Gaya belajar merupakan cara menerima, memahami, dan mengolah informasi dari setiap siswa dalam proses pembelajaran. Pada perkembangannya, gaya belajar secara garis besar (umum) terbagi menjadi gaya belajar visual, auditori, dan kinestetik. Salah satu upaya yang dapat dilakukan agar dapat mengetahui gaya belajar setiap siswa ialah dengan asesmen diagnostik non-kognitif, terlebih dalam kerangka kurikulum merdeka belajar menjadi satu hal yang utama dan penting. Asesmen diagnostik non-kognitif sangat membantu pendidik dalam memetakan kebutuhan dan tujuan pembelajaran sesuai dengan gaya belajar para siswanya. Tidak terkecuali di SMPN 3 Lembang melakukan hal yang sama yaitu dengan melalukan tes diagnostik non-kognitif terhadap 318 siswa sebagai sampel dalam penelitian. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, adapun alat pengumpulan data diambil dari hasil tes diagnostik non-kognitif gaya belajar belajar siswa kelas 7D-7K di SMPN 3 Lembang Tahun pelajaran 2023/2024. Hasil penelitian menunjukkan bahwa gaya belajar siswa kelas 7D-7K di SMPN 3 Lembang paling dominan ialah gaya belajar visual dengan prosentase sebesar 46% (148 siswa), diposisi kedua yaitu gaya belajar kinestetik sebesar 40% (126 siswa), dan gaya belajar auditori sebesar 14% (44 siswa). Diharapkan pendidik dapat menggunakan gaya belajar yang dapat menstimulus gaya belajar visual siswa seperti penggunaan metode mengajar demonstrasi, praktikum, observasi lingkungan sekitar dan lainnya.